PERSPEKTIF BARU PENELITIAN KONSELING: METODE KUALITATIF DAN KUANTATIF SECARA ONLINE - Sugandi Miharja (UIN Kiai Haji Achmad Siddiq Jember, 2022)
This paper attempts to present the use of online media in counseling research. The online research method is a new trend, where researchers can collect data through the internet media. With that being said, thereâ€™s a question arises, â€œwhat is the best online mediaâ€ so that research gets data that meets the validity standards in scientific research. The research was conducted at the Aleogama Porto Guidance Counseling community, which is located at the Aleogama.com website, in Bandung. They carry out counseling service activities using quantitative and qualitative data in an integrated manner. This research approach uses a qualitative study. The data were collected using observation, documentation and interviews. Observations are aimed at the online service process. Documentation in the form of applications and printed data. The interviews were aimed at the components of their human resources, including public relations, coordinators, hosts, testers and administrators. The results of data collection show that using both quantitative and qualitative approaches, the use of online media can provide time effectiveness, maximize human resources and reduce costs in conducting research. A more detailed explanation of the strengths, weaknesses and ways of obtaining data by the research subjects either through questionnaires, surveys or interviews, for counseling research is also described. Either with or without the regulations validated to minimize direct physical contact, online media has contributed effectively in developing the research and theory concerned.